Dealing with Drought‐Related Credit and Liquidity Risks in MFIs: Evidence from Africa1. (January 2015) - Castellani, Davide; Cincinelli, Peter
<x xml:space="preserve">Abstract</x> The credit and liquidity risks of most African MFIs are strongly affected by drought shocks and, even though some traditional asset–liability management strategies are somewhat useful for MFIs to deal with drought risk, innovative risk‐transfer mechanisms are required.